PREVALENCE OF POST-STROKE DEPRESSION IN ADULTS PRESENTING TO RECEP TAYYIP ERDOGAN HOSPITAL, MUZAFFAR GARH (The Research of Medical Science Review, 2025)
Objectives: To determine the prevalence of post-stroke depression (PSD) in patients presenting to Recep Tayyip Erdogan Hospital, Muzaffargarh. Study Design: Descriptive Cross-Sectional Study.Study Setting: The study was conducted at Department of Internal Medicine and Neurology, Recep Tayyip Erdogan Hospital (RTEH), Muzaffargarh.Study Duration: Six months (From September’2024 to Febuary’2025.Methodology: This study enrolled 229 patients aged 18–70 years with ischemic or hemorrhagic stroke confirmed by imaging within the past year. Patients were evaluated using the Patient Health Questionnaire-9 (PHQ-9), where a score ≥5 indicated depression. Sociodemographic and clinical data including age, gender, marital status, BMI, smoking, and diabetes were recorded. Results: Of the 229 participants, 52.4% were female and 60.7% were aged 18–50 years. The mean age was 44.43 ± 15.51 years and mean duration since stroke was 6.80 ± 3.39 months. The prevalence of post-stroke depression was found to be 27.1%. No statistically significant associations were found between PSD and age group (p=0.423), gender (p=0.884), or marital status (p=0.573). Conclusion: More than one in four stroke survivors experienced depressive symptoms, underscoring the need for routine mental health screening post-stroke. Despite the lack of significant associations with basic demographic factors, early detection through tools like PHQ-9 is essential for timely intervention and improved rehabilitation outcomes.